PEMBENTUKAN STRUKTUR PORTOFOLIO MENGGUNAKAN MODEL BETA PADA INDUSTRI PERTANIAN DAN PERTAMBANGAN DI BURSA EFEK INDONESIA - Lestari, Lestari (Research Institution and Community Service Wijaya Kusuma Surabaya University, 2017)
The main objective of investors in making investments is to gain profit (Return). To maximize expected returns, investors do a strategy that can increase returns or can reduce risk. Because investors basically love investments that generate high returns, but do not really like the risk One strategy that can be used in forming an optimal portfolio structure is to look at the risks and returns of each stock that enter the portfolio structure. Meanwhile, to estimate the amount of risk and the amount of return that will be offered. One model to estimate the magnitude of the risk of securities (shares) is by beta method. Then choose an industry or a group of industries that have good financial performance or industry that is easy / resistant to the onslaught of various internal environmental changes both economic, political, market and other aspects. Some industries that are resistant to the onslaught are agriculture sector and mining sector. Based on the above description, this research tries to raise the theme related to the Formation of Portfolio Structure Using Beta Model in Agriculture and Mining Industry in Indonesia Stock Exchange.